From mouth to macrophage: mechanisms of innate immune subversion by Mycobacterium avium subsp. paratuberculosis - Arsenault, Ryan J (BioMed Central, 2014)
Johne’s disease (JD) is a chronic enteric infection of cattle caused by Mycobacterium avium subsp. paratuberculosis (MAP). The high economic cost and potential zoonotic threat of JD have driven efforts to develop tools and approaches to effectively manage this disease within livestock herds. Efforts to control JD through traditional animal management practices are complicated by MAP’s ability to cause long-term environmental contamination as well as difficulties associated with diagnosis of JD in the pre-clinical stages. As such, there is particular emphasis on the development of an effective vaccine. This is a daunting challenge, in large part due to MAP’s ability to subvert protective host immune responses. Accordingly, there is a priority to understand MAP’s interaction with the bovine host: this may inform rational targets and approaches for therapeutic intervention. Here we review the early host defenses encountered by MAP and the strategies employed by the pathogen to avert or subvert these responses, during the critical period between ingestion and the establishment of persistent infection in macrophages.